Assessing the feasibility of local agro-waste for amylase production by Aspergillus niger via SSF - Nurul Shuhada, binti Daud. (Universiti Malaysia Sarawak (UNIMAS), 2016)
Local agriculture wastes such as rice husks, cassava peels and banana peels were used as the solid state fermentation substrate for the producing ofamylase enzyme by Aspergillus niger. The objectives ofthis project were to identify local agro-wastes that give the highest enzyme activity and to determine the optimum solid state fermentation condition for maximum activity of amylase. Three important solid state fermentation parameters were studied; incubation period, temperature and initial moisture content. Based on the results, the optimal temperature was at 37°C for 70 % ofinitial moisture content and 6 days of incubation period. The rice husk was the best substrate for A. niger to produce the highest activity of amylase.